2012
DOI: 10.1113/expphysiol.2011.061374
|View full text |Cite
|
Sign up to set email alerts
|

Local sweating on the forehead, but not forearm, is influenced by aerobic fitness independently of heat balance requirements during exercise

Abstract: The present study investigated the influence of maximal oxygen uptake (V O 2 max ) on local steadystate sudomotor responses to exercise, independently of evaporative requirements for heat balance (E req ). Eleven fit (F;V O 2 max 61.9 ± 6.0 ml kg −1 min −1 ) and 10 unfit men (UF;V O 2 max 40.4 ± 3.8 ml kg −1 min −1 ) cycled for 60 min at an air temperature of 24.5 ± 0.8 • C and ambient humidity of 0.9 ± 0.3 kPa at a set metabolic heat production per unit surface area, producing the same E req in all participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…It also remains uncertain whether isothermic heat acclimation is a more efficient method than fixed intensity heat acclimation for preparing highly trained individuals for exercise heat stress (Garrett et al, 2012). Highly trained individuals are likely to be able to sustain the greater absolute workloads required of the isothermic methods, with higher metabolic heat production elevating the rate of core temperature more rapidly (Cramer et al, 2012;Garrett et al, 2012Garrett et al, , 2011 and thus, giving greater competition specificity to their acclimation, further enhancing the efficacy of isothermic methods for this population.…”
Section: Future Research Directionsmentioning
confidence: 97%
“…It also remains uncertain whether isothermic heat acclimation is a more efficient method than fixed intensity heat acclimation for preparing highly trained individuals for exercise heat stress (Garrett et al, 2012). Highly trained individuals are likely to be able to sustain the greater absolute workloads required of the isothermic methods, with higher metabolic heat production elevating the rate of core temperature more rapidly (Cramer et al, 2012;Garrett et al, 2012Garrett et al, , 2011 and thus, giving greater competition specificity to their acclimation, further enhancing the efficacy of isothermic methods for this population.…”
Section: Future Research Directionsmentioning
confidence: 97%
“…(14)(15)(16)(17)(18) A caveat, however, is that these studies typically employed a similar relative exercise intensity pre-and post-training, such that the absolute exercise and thus metabolic heat production and thermal stress were higher post-training. Recent studies demonstrated no difference in core temperature rise before sweating onset, nor sweating thermosensitivity, when absolute exercise intensity, and hence metabolic heat production, was controlled (19,20) . Nevertheless, the potential for physical training to complement or partially supplant traditional heat acclimatization can be particularly attractive for workers tasked with performing in hot environments who, because of other job requirements, lack of heat acclimation facilities, or rapid field deployment, may not be able to devote the necessary time for longer duration heat adaptation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increasing body temperature alone can alleviate symptoms of depression in depressed patients (Hanusch et al 2013; Koltyn et al 1992) and depressed individuals have deficits in thermoregulatory cooling (Ward et al 1986). Additionally, individuals who are exercise trained activate thermoregulatory cooling mechanisms more efficiently than untrained controls (Cramer et al 2012; Ichinose-Kuwahara et al 2010). Thus it seems plausible that the antidepressant-like effects of exercise may depend, in part, on alterations in thermoregulation; however the potential mechanisms remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%